Fulfillment of the Rights of Children with Disabilities in Inclusive Education in the Digital Era: Evidence from Gorontalo City - Makkulawuzar, Kindom; De La Cruz, Mawardi; Lahaling, Hijrah (Al-Adalah: Jurnal Hukum dan Politik Islam, 2026)
Inclusive education constitutes a fundamental human right, yet children with disabilities in Gorontalo City face persistent barriers in accessing it. This study analyzes the legal framework governing inclusive education rights and evaluates the implementation of adaptive, technology-supported inclusive policies. Employing a socio-legal approach with a descriptive–analytical design, the research integrates normative analysis of legal instruments with empirical data from focus group discussions, interviews, and document review. Findings reveal that Regional Regulation No. 3 of 2023 has not been effectively operationalized, with implementation hindered by systemic factors (insufficient qualified teachers, non-adaptive curricula, inadequate accessible infrastructure), socio-cultural factors (stigma and bullying), and digital factors (limited device access and low digital literacy). The results highlight a substantial gap between normative guarantees and practical implementation. The study underscores the need for operational regulations, enhanced teacher capacity, accessible digital learning facilities, and multi-stakeholder collaboration to achieve an equitable and inclusive educational ecosystem.